Longitudinal assessment of migraine burden in resistant and refractory migraine – Data from the prospective REFINE study - Umberto Pensato; Raffaele Ornello; Chiara Rosignoli; Valeria Caponnetto; Agnese Onofri; Mark Braschinsky; Olga Sved; Raquel Gil-Gouveia; Renato Oliveira; Christian Lampl; Jakob Paungarttner; Paolo Martelletti; et al. (The Journal of Headache and Pain)
Abstract Background Some individuals with migraine fail to respond adequately to preventive treatments, bearing most of migraine burden. The European Headache Federation (EHF) classifies these individuals into resistant migraine (ResM) or refractory migraine (RefM) according to treatment failures, debilitating headache days, and disease duration. We investigated the evolution of these categories over six months in patients treated at tertiary headache centers and whether they accurately reflect disability and burden. Methods Participants from the multicenter, prospective REFINE study were classified into three categories of treatment responsiveness, namely RefM, ResM, and non-refractory non-resistant migraine (NRNRM). The primary objective was to determine the trajectories of category changes over six months. Secondary outcomes included changes in the 6-item Headache Impact Test (HIT-6), Headache-Attributed Lost Time (HALT), and Hospital Anxiety and Depression Scale (HADS-A and HADS-D) scores. Results Overall, 489 participants were included with a median age of 45 years (IQR = 36–53); 389 participants (79.7%) were female; 256 (52.4%) had NRNRM, 178 (36.4%) ResM, and 55 (11.2%) RefM. At follow-up, 200/256 (78.1%) NRNRM remained stable, while 56/256 (21.9%) progressed to ResM. Among those with ResM, 98/178 (55.1%) remained stable, 72/178 (40.5%) improved to NRNRM, and 8/178 (4.5%) worsened to RefM. Among participants with RefM, 37/55 (67.3%) remained stable, while 18/55 (32.7%) improved to NRNRM. Participants with RefM and ResM presented significantly higher scores at baseline than those with NRNRM. Over time, HIT-6, HALT, and HADS-A scores improved substantially in the overall cohort (p < 0.001, p < 0.001, and p = 0.006, respectively). Improvements were observed in participants with ResM across all scores and HIT-6 and HALT for NRNRM, but no improvement was noted in participants with RefM. Conclusions Over six months, ~ 40% of ResM and ~ 30% of RefM individuals improved to NRNRM, while ~ 20% of NRNRM developed treatment resistance after receiving care in tertiary headache centers. Participants with ResM had a better prognosis than those with RefM. While both ResM and RefM reflect high migraine disability burden, they might present relevant differences in their management and prognosis.